ENTEROCOCCUS AND ENTEROCOCCUS-LIKE ORGANISMS RECOVERED IN FAECAL SCREENING FOR VANCOMYCIN-RESISTANCE - Hristina Y. Hitkova; Preslava M. Hristova (Peytchinski Publishing, 2019)
Background: Fecal screening of patients for vancomycin-resistant enterococci (VRE) is recommended in an attempt to establish infection control measures. Culture-based methods for VRE detection are widely used, but particular attention should be paid to correct identification of growing isolates. This study is focused on species identification and antimicrobial susceptibility of vancomycin-resistant enterococci and other Gram-positive catalase-negative cocci, recovered from VRE screen cultures. Materials and methods: A total of 109 immunocompromised patients from University Multiprofile Hospital for Active Treatment "Dr G. Stranski", Pleven were screened for VRE. The determination of cocci was relied on cultural characteristics, manual and automated systems for identification as well as data on antimicrobial sensitivity. Results: A total of 57 Gram-positive catalase-negative cocci were isolated: 32 VRE, 11 vancomycin-susceptible enterococci and 14 enterococcus-like organisms. Colonization with VanA or VanC enterococci was detected in 29.35% of the patients, with a distinct prevalence of VanC (23.85%) over than VanA(5.50%). Six enterococci were confirmed as vanA genotype- 5 E. faecium and 1 E. gallinarum. All E. faecium isolates expressed high-level resistance to vancomycin (MICs ≥256 µg/ml) and low-level resistance to teicoplanin (MICs: 4.0-6.0 µg/ml), whereas a single E. gallinarum isolate showed MICs ≥256 µg/ml for both glycopeptides. The isolated VanC enterococci (13 E. gallinarum and13 E. casseliflavus) were susceptible to tested antibiotics and possessed low-level resistance to vancomycin (MICs: 4-12 µg/ml). Most of the recovered enterococcus-like organisms were identified as Leuconostoc spp. In conclusion, both species identification and antimicrobial susceptibility pattern have to be taken into account for distinguishing VRE and other Gram-positive catalase-negative cocci, growing in VRE screen cultures.